Pasar Pelita Kecamatan Kubu Babussalam Dengan Pendekatan Arsitektur Neo-Vernacular - Muhammad Rafiki; Wahyu Hidayat; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Pelita Market is one of the markets in Kubu Babussalam sub-district, precisely in Simpang Pelita village, Rokan Hilir district. Judging from the location of the lamp market position, it is in astrategic position that is on the edge of the traffic road, so that access to the market does not get obstacles, because it has been equipped with adequate transportation. However, various commonproblems that occur in traditional markets still occur in the Pelita Market, such as physical buildings that are no longer suitable for use, irregular trade area arrangements, poor managementof circulation patterns (people, goods and vehicles), and a minimum market supporting facilities and infrastructure such as parking areas, garbage bins, security systems and so on. This lampmarket is located on Jalan Jenderal Sudirman, precisely in Rantau Panjang Kiri village, Kubu Babussalam sub-district. The problem in this lamp market is the merchants who sell at the edge ofthe road with tents piled along the road causing the road to become narrow and congested.Keyword: Pelita Market In The Subdistric of Babussalam